1998
DOI: 10.1016/s0014-5793(98)00920-x
|View full text |Cite
|
Sign up to set email alerts
|

Protein phosphatase inhibitors and heat preconditioning prevent Hsp27 dephosphorylation, F‐actin disruption and deterioration of morphology in ATP‐depleted endothelial cells

Abstract: The vascular endothelium response to ischemic depletion of ATP was studied in vitro. Endothelial cells (EC) cultured from human aorta or umbilical vein were incubated in a glucose-free medium containing CCCP or rotenone. Such blockade of energy metabolism caused a drop in ATP, destruction of actin filaments, morphological changes, and eventually disintegration of EC monolayer within 2-2.5 h. While ATP fell and F-actin collapsed, the 27-kDa heat shock protein (Hsp27) lost basal phosphorylation and became Triton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 35 publications
(55 reference statements)
4
31
0
Order By: Relevance
“…Previously, quercetin was shown to abolish the heat preconditioning-induced stabilization of F-actin in ATP-depleted endothelial cells, which suggested the protective role for stressinduced HSPs (21,22). In the present study, quercetin, when added to H9c2 cells, did not affect normal morphology (not shown) and restoration of the ATP level following the metabolic preconditioning (Fig.…”
Section: Elevated Resistance To Atp Depletion-induced Cell Death In Tsupporting
confidence: 60%
See 1 more Smart Citation
“…Previously, quercetin was shown to abolish the heat preconditioning-induced stabilization of F-actin in ATP-depleted endothelial cells, which suggested the protective role for stressinduced HSPs (21,22). In the present study, quercetin, when added to H9c2 cells, did not affect normal morphology (not shown) and restoration of the ATP level following the metabolic preconditioning (Fig.…”
Section: Elevated Resistance To Atp Depletion-induced Cell Death In Tsupporting
confidence: 60%
“…Recovery periods following either priming stress continued for 16-18 h before the challenging ATP depletion. Quercetin was added at a 30 M concentration to some samples of the cells before the stressful preconditioning (21,22); this drug was present in the incubation medium during the priming stress and the next 10 h, and then the drug-containing medium was replaced by the usual growth medium. To perform the challenging ATP depletion, we placed the cells in the CCCPcontaining medium supplemented with 10 mM 2-deoxyglucose and incubated them at 37°C in a CO2 incubator (21,22).…”
Section: Cellsmentioning
confidence: 99%
“…For example, swelling-induced damage is a pivotal mechanism of injury during ischemia and reperfusion (60,61); thus, HSP27-mediated cell strengthening in ischemia/reperfusion would be a potential mechanism of endogenous cardioprotection. This would be consistent with a number of cellular studies showing that small HSPs provide protection against simulated ischemia involving a hypotonic stress that causes swelling-induced damage (57,(62)(63)(64)(65)(66).…”
Section: Biotin-cysteine As a Probe For Proteins That Are S-thiolatedsupporting
confidence: 90%
“…Dynamic functions of the actin cytoskeleton, meditated through shifts in monomeric (G-actin) and filamentous (Factin) actin levels, play an important role in cellular morphology and permeability of the vascular endothelium (22). Progressive disassembly and shortening of the microfilaments of endothelial cells were observed during ATP depletion, and rapid reassembly was seen during cell recovery (24,25,33). Previous in vivo studies have evaluated actin cytoskeletal changes during ischemic injury (31,48).…”
mentioning
confidence: 99%